To determine if \( x = -3 \) is a solution to the quadratic equation \( -3x^2 - 9x = 0 \), we need to substitute \( -3 \) into the equation and evaluate.
Substituting \( x = -3 \) into the equation:
\[ -3(-3)^2 - 9(-3) = 0 \]
Calculating each term:
- \( (-3)^2 = 9 \) so \( -3(9) = -27 \)
- \( -9(-3) = 27 \)
Now combine these results:
\[ -27 + 27 = 0 \]
This simplifies to:
\[ 0 = 0 \]
Since this statement is true, \( x = -3 \) is indeed a solution to the equation.
Therefore, the correct explanations are:
Yes, x = -3 is a solution because substituting it back into the equation results in the following:
-3(-3)^2 - 9(-3) = 0 0 = 0 True
This corresponds to the responses that state \( 0 = 0 \) upon substitution, confirming it as a valid solution.